Relationship between type of delivery and colostrum production from postpartum mothers at Dr.H.Moch Ansari Saleh Hospital, Banjarmasin - Cantika Cantika; Fadhiyah Noor Anisa; Fitri Yuliana; Sarkiah Sarkiah (Sean Institute, 2023)
Colostrum is a yellowish liquid that is produced from pregnancy to 4 days postpartum. However, colostrum cannot be secreted directly because levels of the hormone estrogen are still high. Delays in expressing colostrum can affect exclusive breastfeeding. The choice of type of delivery has an impact on the occurrence of colostrum production in postpartum mothers. Mothers who give birth normally have the opportunity to immediately give colostrum to their babies through the IMD process or early contact. This study aims to analyze the relationship between type of delivery and colostrum expenditure at RSUD Dr. H. Moch Ansari Saleh Banjarmasin. This type of research is quantitative with a cross sectional design. The respondents in this study were 108 postpartum mothers, taken using a purposive sampling technique as many as 37 people, then analyzed using the Chi-Square test. Data was obtained from 37 postpartum mothers based on the most age characteristics, namely <20 and >35 years (51%), multiparous parity 21 people (57%), nutritional status ≥23.5 cm (97%), basic level education as many as 25 people (67.6%), SC delivery (59.5%). The highest colostrum production is >120 minutes. The results of Chi-Square analysis obtained valuesp value0.000 (p<0.05)which means accepting the alternative hypothesis, meaning that there is a real relationship between the type of delivery and colostrum expenditure. It can be concluded that there is a relationship between the type of delivery and colostrum expenditure. This is because the SC type of delivery slows down the time of colostrum expulsion, occurring at >120 minutes.